2018
DOI: 10.1177/0146167218796473
|View full text |Cite
|
Sign up to set email alerts
|

Ego Depletion Reduces Attention Control: Evidence From Two High-Powered Preregistered Experiments

Abstract: Two preregistered experiments with over 1000 participants in total found evidence of an ego depletion effect on attention control. Participants who exercised self-control on a writing task went on to make more errors on Stroop tasks (Experiment 1) and the Attention Network Test (Experiment 2) compared to participants who did not exercise self-control on the initial writing task. The depletion effect on response times was non-significant. A mini meta-analysis of the two experiments found a small (d = 0.20) but … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 54 publications
4
62
0
Order By: Relevance
“…To avoid such practices, recently published studies of ego depletion have often been pre-registered (e.g., Alquist et al, 2018;Garrison, Finley, & Schmeichel, 2018) or highly transparent (e.g., Francis, Milyavskaya, Lin, & Inzlicht, 2018). To address the weaknesses of traditional depletion manipulations with a short duration or weak intensity (e.g., Letter 'e' task; Baumeister, Bratslavsky, Muraven, & Tice, 1998), recent research has also used different manipulation tasks (e.g., Blain, Hollard, & Pessiglione, 2016;Sj astad & Baumeister, 2018).…”
mentioning
confidence: 99%
“…To avoid such practices, recently published studies of ego depletion have often been pre-registered (e.g., Alquist et al, 2018;Garrison, Finley, & Schmeichel, 2018) or highly transparent (e.g., Francis, Milyavskaya, Lin, & Inzlicht, 2018). To address the weaknesses of traditional depletion manipulations with a short duration or weak intensity (e.g., Letter 'e' task; Baumeister, Bratslavsky, Muraven, & Tice, 1998), recent research has also used different manipulation tasks (e.g., Blain, Hollard, & Pessiglione, 2016;Sj astad & Baumeister, 2018).…”
mentioning
confidence: 99%
“…Similarly, studies that employed other depleting tasks also yielded results from which no definitive conclusion could be drawn, with some studies reporting substantive, non-zero effects (Bayer & Osher, 2018;Dang, Liu, Liu, & Mao, 2017;Garrison, Finley, & Schmeichel, 2019) while others reporting effects that were no different from zero (Etherton, Osborne, Stephenson, Grace, Jones, & De Nadai, 2018;Lurquin et al, 2016;Singh & Göritz, 2018).…”
Section: Addressing Replication Issuesmentioning
confidence: 99%
“…Concerns include the fact that depletion research often involves small samples, that it likely suffers from publication bias, and that it sometimes fails to produce the expected effect (for a summary of criticisms, see Friese, Loschelder, Gieseler, Frankenbach, & Inzlicht, ). For example, a meta‐analysis of 116 studies found no evidence of a depletion effect (Carter, Kofler, Forster, & McCullough, ), but critics have argued the correction techniques used in this analysis were flawed (Garrison, Finley, & Schmeichel, ). Similarly, a high‐powered replication study conducted across multiple labs failed to find the effect (Hagger & Chatzisarantis, ); however, these studies have been criticized for employing an invalid self‐control manipulation (Baumeister & Vohs, ).…”
Section: The Battle Between Temptation and Restraintmentioning
confidence: 99%
“…Similarly, a high‐powered replication study conducted across multiple labs failed to find the effect (Hagger & Chatzisarantis, ); however, these studies have been criticized for employing an invalid self‐control manipulation (Baumeister & Vohs, ). More recent replication attempts using large (1,000+) samples and pre‐registered methods found evidence that prior exertion did have a small but significant impact on subsequent self‐control performance (Garrison et al, ; Wagenmakers & Gronau, ).…”
Section: The Battle Between Temptation and Restraintmentioning
confidence: 99%